Sum  to  n    terms      


 


3.7.11.15+7.11.15.19+................... 


 


Dont post the full solution,Maybe Hints(Like the method )


 


Should we use factorial things in here???


 


 

2 years ago

Share

Answers : (14)

                                        

The biggest hint to theis problem tht the question can be done using Vn method. Search it. Try it

2 years ago
                                        

Do u know the Vn method ??

2 years ago
                                        

At Swapnil Saxena : Thanks for the hint.How do u know these kinda of methods?




V-n method




V-n method is used to solve the series summation problem in the fom of :


 


1> 1/(a1*a2)  +  1/(a2*a3)  +  1/(a3*a4)  +........ upto n terms


 


2>(a1*a2)  + (a2*a3)  +  (a3*a4)  +.............upto n terms


 


where a1,a2,a3 ..... are in AP with certain common difference


 

2 years ago
                                        

hi swapnil


this question cannot be done by VN method!!!!


see and guess why this question is not done by VN method

2 years ago
                                        

@ Samarth : No Idea??? Why... Tell me. Is there is something wrong. This is wht u told me.


@ Sathyaram : Good Friendship, attempts, courage, and hard labour always pays...


@ Jit: Sathyaram is right... but I wanna further extend . Not just the series like tht but like


a1a2a3a4a5+ a2a3a4a5a6 +a3a4a5a6a7 .... or 1/a1a2a3a4a5+ 1/a2a3a4a5a6 + 1/a3a4a5a6a7 ....  like difficulties can be solved by this method  

2 years ago
                                        

Hi Guys,


 


This question can definitely be solved using the Vn method.


S = Σ(4r-1)(4r+3)(4r+7)(4r+11), r=1,2,3,....n.


So Tr = (4r-1)(4r+3)(4r+7)(4r+11)


and let Vr = (4r-5)(4r-1)(4r+3)(4r+7)(4r+11)


hence, Vr+1 = (4r-1)(4r+3)(4r+7)(4r+11)(4r+15)


 


So Vr+1 - Vr = 20xTr.


Hence Σ(Vr+1 - Vr) = 20*S


Hence S = (1/20)*[Vn+1 - V1] = (1/20)*[(4n-1)(4n+3)(4n+7)(4n+11)(4n+15) + 3.7.11.15] ------- (Required Answer).


 


Regards,


Ashwin (IIT MadraS).

2 years ago
                                        

Agree with swapnil. Lemme try to generalize it for u.


 


S = a1a2a3a4a5....ar + ar+1ar+2ar+3ar+4....a2r +    ..............  + an-r+1an-r+2an-r+3......an


 


Tn = an-r+1an-r+2an-r+3......an


 


Vn = anan+1an+2......an+r-1an+r


(Take an extra Last Term in Vn)


 


Vn-1 = an-1anan+1......an+r-2an+r-1


 


Vn - Vn-1 = anan+1an+2......an+r-1 [an+r - an-1 ] = Tn[an+r - an-1 ] = Tn [{a1 + (n+r-1)d} - {a1+ (n-2)d}] = Tn [(r+1)d]


 


or, Tn = 1/[(r+1)d] * [Vn - Vn-1]


 


Now put n=1,2,3,....,n and add.


 


T= 1/[(r+1)d] * [V1 - V0]


T= 1/[(r+1)d] * [V2 - V1]


T= 1/[(r+1)d] * [V3 - V2]


.


.


.


.


T= 1/[(r+1)d] * [Vn - Vn-1]


______________________________


S = 1/[(r+1)d] * [Vn - V0]


 


From here you can find the sum easily.


 


Similarly for the sum of reciprocals, Take one term less for Vn .

2 years ago
                                        

@ Ashwin Sir,


Thanks for ur answer and ur answer is correct...


 


But, How could u assume that "let Vr = (4r-5)(4r-1)(4r+3)(4r+7)(4r+11)"?


 


And where did (4r-5) go in this equation? :


Vr+1 = (4r-1)(4r+3)(4r+7)(4r+11)(4r+15)

2 years ago
                                        

Dude,


 


Enna idhu Sir lam... :P


Seri adhe vidu.


 


Vr is assumed based on the Tr.


In Vr we assume one more term in the start.


 


If Vr = (4r-5)(4r-1)(4r+3)(4r+7)(4r+11)


then replace r by r+1 in this to get Vr+1.


Hence you get Vr+1.


 


Regards,


Ashwin (IIT Madras).

2 years ago
                                        

Pingilikka pillaaapi ,Summa said.


 


Can u do this without Vn method ?I am kinda new to this and not feelin comfortable...

2 years ago
                                        

Dude,


 


Then please get comfortable with it.


It is really easy.


 


Regards,


Ashwin (IIT Madras),

2 years ago
                                        

Periya manishan,Neenga solitengala.......Ill get comfortable  :)  Laughing  


 


And also,I have send u sme mails in gmail......Pls look at it

2 years ago
                                        

Dude,


 


Done!!


Hope that you take those mail replies seriously. Now you prepare and do your Boards well.


 


You can think about your 11th Std after your exams :).


Wish you all the best.


 


Regards,


Ashwin (IIT Madras).

2 years ago
                                        

Oh k.Thnks.I have sent u  reply....Pls look at it and dont forget to c mokkais ! Tongue out


And in Biology CBSE,


I dont understsnd these mendels cross breeding,dominant,recessice...Could u just help me out... :)

2 years ago

Post Your Answer

More Questions On Algebra

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
If 1,w,w2 are cube roots of unity, prove that (1-w)(1-w2)(1-w4)(1-w5) = 9
 
 
We have 1 + w + w 2 = 0 & w 3 = 1 (1 – w)(1 – w 2 )(1 – w 4 )(1 – w 5 ) = (1 – w)(1 – w 2 )(1 – w 3 .w)(1 – w 3 .w 2 ) = (1 – w)(1 – w 2 )(1 – w)(1 – w 2 ) (Since w 3 = 1) = (1 – w) 2 (1 – w...
 
Y RAJYALAKSHMI one month ago
i have 2 questions --- The Condition that the roots of the eqn ax 2 + bx + c = 0 such that one root is n times the other is : a) na 2 = bc(n+1) 2 b) nb 2 = ca (n+1) 2 c) nc 2 =ab(n+1) 2 2....
 
 
Hello student, Please find the answer to your question below 1)let the roots be x,xn so x+xn=(-b/a) and x 2 n=c/a x=(-b/a(n+1)).........(1) and also x 2 =(c/an).......(2) substituting 1 in 2...
  img
SHAIK AASIF AHAMED 3 months ago
Factorise a 3 – 27b 3 – 7ab 2 + 21a 2 b
 
 
Divide by b 3 and replace (a/b) by x ; we get, x 3 + 21x 2 _ 7x –27 = 0; Notice if x = -1 then it reduces to 0; .: (x+1) is a factor ; Now divide the equation by (x+1) we get, x 2 + 20x – 27...
 
MANU MITRAAN 2 months ago
evaluate ∫ (sqrt(x)( ax^2 + bx + c)) dx
 
 
∫ (sqrt(x)( ax^2 + bx + c)dx =​∫ (x^1/2(ax^2 +bx +c)dx =​∫ (ax^5/2 +bx^3/2 +cx^1/2)dx =2​ax^7/2 /7 +2bx^5/2 /5 +2cx^3/2 /3 +K {we know that​∫x^ndx =(x^(n+1) /(n+1)} Here K is...
  img
Sunil Raikwar 3 months ago
 
make ax 2 +bx+c in to form of a((x-b/2) 2 +(c -b 2 /4)). then put (x-b/2)=(c-b 2 /4)^.5*tany. then integrate it. simple
 
Karthick vel 3 months ago
the normal to the curve at P(x,y) meets the x axis at G. If the distance of G from the origin is twice the abscissa of P , then the curve is a) ellipse b) parabola c) ellipse or hyperbola
 
 
solution: for any curve the equation of normal at ( X1, Y1) (y- y1) = -1/m (x- X1) {where m = slope of tengent or say dy/dx at (x1, Y1) } normal meets the X axis at G.. so ( 0 - y1) = -1/m...
  img
Ajay Verma 8 months ago
 
but sir the answer says it can be both ellipse as well as hyperbola, so can u please prove this as an ellipse too.
 
vansh kharbanda 7 months ago
 
thank you
 
vansh kharbanda 7 months ago
3 ∫ 2 (2x 2 + 1) dx
 
 
integration of (2(X^2)+1)dx from 2 to 3 is equal to (2((x^3)/3)+x) from 2 to3 =(2((3^3)/3)+3)-(2((2^3)/3)+2) =(2*(27/3)+3)-(2*(8/3)+2) =(18+3)-((16/3)+2) =(21)-(22/3) =41/3
 
Miryala Gopalakrishna 28 days ago
 
Ans:- 3 ∫ 2 (2x 2 +1)dx =2[(x 2+1 /2+1)] 2 3 +[x] 2 3 =2[(x 3 /3)] 2 3 +[x] 2 3 =2[(3 3 /3)+(2 3 /3)]+[3-2] =2[(27+8)/3]+1 =2[(35/3)]+1 =(70/3)+1 =73/3
 
Anusha 28 days ago
View all Questions »